RERATA VOLUME TROMBOSIT DAN AGGREGASI TROMBOSIT DI DIABETES MELITUS TIPE 2 (Mean Platelet Volume and Platelet Aggregation in Diabetes Mellitus Type 2) - Malayana Rahmita Nasution; Adi Koesoema Aman; Dharma Lindarto (Indonesian Association of Clinical Pathologist and Medical laboratory, 2015)
Diabetes mellitus patients often have hypercoagulable blood, as evidenced by the increased coagulation, impaired fibrinolysis,endothelial dysfunction and platelet hyperactivity. Hyperactive platelet is the major determinant of pro thrombotic state in DM. Byassessing the MPV and platelet aggregation, which is a marker of platelet activity, in patients with type 2 DM, it is expected to help theprediction of acute events. This research is aimed to know the differences of MPV and the aggregation of platelet between poor glycemiccontrol as well as good the control group in type 2 DM patients. This study was conducted in cross sectional method using 22 people withgood glycemic control and 28 people with poor one (glycemic control) from June to August 2013. Fasting blood samples were analyzedfor CBC, HbA1c, TG and platelet aggregation. MPV and platelet aggregation value were compared between groups using independentt-test. Based on this study, there is no significant difference in MPV and platelet aggregation between groups (p=0.598, p=0.464 (1 μM),p=0.868 (2 μM), p=0.984 (5 μM), p=0.401 (10 μM)). Mean Platelet Volume (MPV) correlate significantly with platelet aggregationat 1 μM and 5μM ADP concentration in good glycemic control group (r=0.591; p=0.004 at 1 μM ADP and r=0.521; p=0.013 at 5 μMADP). Mean platelet volume correlate significantly with the platelet aggregation at 2 μM ADP and the concentration in poor glycemiccontrol group (r=0.405; p=0.033). There are no significant differences in MPV and platelet aggregation between groups, but there is asignificant correlation between them (MPV and platelet aggregation) in the good glycemic control of the type 2 DM group.